Post Thawing Sperm Quality and Ca+2 Intensity Characters of Local Goat Sperm After Freezing by Simple Method Using Deep Freezing - Gatot Ciptadi; Muhammad Nur Ihsan; Sri Rahayu; Sri Wahjuningsih; Anis Mei Munazaroh; R. P. Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
The objective of this research was to determine the effect of the simple modified freezing method, 1°C/minute freezing rate with different diluter ration on a post-thawing quality of local goat sperm namely Peranakan Etawah (PE). This work is aimed to study the quality of post-thawing sperm and to characterize the calcium intensity profile of both fresh and post thawing goat sperm. The method used is the experimental design of a laboratory. Freezing semen was performed in 2 main temperatures of -45°C then -196°C respectively using Mr. Frosty (®) System. Early Sperm characters of Ca+2 intensity was performed by Confocal Laser Scanning Microscope (CLSM) through Fluo-3 staining and Ca++ intensity was analysis descriptively. The result showed that post-thawing qualities are considered as good as standard qualities, at least, more than 40% based on Indonesian National Standard (SNI, 2014). The different level diluents commercial of Andromeda used were influenced highly significant (P<0.01). The best diluents ration is 1:4 (v/v) for final sperms stocked at -196°C. However freezing sperm conserved in -196°C is better than in -45°C. Meanwhile, the sperm characters of two condition showed the important variation of Ca+2 intensity, with the length of region measurement of 39.06±4.595 and 32.696±9.011 µm each. It was concluded that the calcium intensity pattern was varied more and higher in fresh sperm than in freezing sperms. This simple modified method of a freezing system was considered as a feasible alternative method for goat semen in a reason for both for sperm post-thawing quality and practical purposes.